EVALUATION OF INFLAMMATORY BIOMARKERS AND THERAPEUTIC INTERVENTIONS IN CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Davron K. Muminov; Farhod T. Musayev (Central Asian Journal of Medicine, 2025)
Aim: to evaluate the effectiveness of different therapeutic interventions in reducing systemic inflammation and improving clinical outcomes in COPD patients. Materials and Methods: The study included 130 participants, comprising 110 patients diagnosed with COPD and 20 healthy individuals as controls. The COPD patients were divided into groups: Group 1 (53 patients, categorized under A and B) and Group 2 (57 patients, categorized under C and D). All participants underwent clinical examinations, lung function assessments, and biomarker analysis at baseline and three-month intervals. Results: Group 1 patients exhibited significantly higher leukocyte counts and pro-inflammatory cytokine levels before treatment than Group 2 (p<0.05). However, CRP levels were twice as high in Group 2 compared to Group 1. A correlation was found between CRP levels, ventilation impairments, and the annual exacerbation rate (AER). After treatment, a significant reduction in inflammatory biomarkers was observed, particularly in Subgroup 1A. Leukocyte count in Subgroup 1A decreased by 13.5% compared to Subgroup 1B, while in Group 2, leukocyte reduction was not statistically significant (p > 0.05). The results suggest that patients in Subgroup 1A experienced a more effective reduction in systemic inflammation than those in Subgroup 1B, demonstrating a superior response to the treatment regimen. Conclusion: The study highlights the importance of targeted therapeutic interventions in managing COPD-related inflammation. However, inflammatory markers remained elevated despite improvements compared to healthy individuals, indicating persistent latent inflammation. These results underscore the necessity for continued anti-inflammatory strategies to optimize COPD management and reduce disease progression.